2021
DOI: 10.23910/1.2021.2378d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oil Cakes and Bio-agents Each Alone and in Combination for Management of Root Knot Nematode (Meloidogyne incognita) in Green Gram

Abstract: A pot experiment was carried out in the net house of Department of Nematology, OUAT, Bhubaneswar, Odisha, India during June to August, 2017 on the application of oilcakes (mustard cake and neem cake) and bio-agents (Trichoderma viride, Glomus fasciculatum, Rhizobium leguminosarum) each alone and in combination for the management of root knot nematode (Meloidogyne incognita) in green gram. Result of the experiment indicated that soil application of mustard or neem cake @ 50 g m-2 with AM fungus (Glomus fascicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They also studied the evidence of induced resistance against T. urticae in Okra plants manured with oil cake based vermicomposts (Mahto and Yadav 2009 a). [21,22] Several previous studies showed that oil cakes have shown major promise as a new strategy in managing nematodes ( [19,18,13,23] and sucking pests including mites (Mahto and Yadav 2009 a, b and Veena et al, 2017). [21,22,30] Therefore, it seems that use of oil cakes can be considered as a fantastic alternative of chemical compounds.…”
Section: Discussionmentioning
confidence: 99%
“…They also studied the evidence of induced resistance against T. urticae in Okra plants manured with oil cake based vermicomposts (Mahto and Yadav 2009 a). [21,22] Several previous studies showed that oil cakes have shown major promise as a new strategy in managing nematodes ( [19,18,13,23] and sucking pests including mites (Mahto and Yadav 2009 a, b and Veena et al, 2017). [21,22,30] Therefore, it seems that use of oil cakes can be considered as a fantastic alternative of chemical compounds.…”
Section: Discussionmentioning
confidence: 99%